LEGAL TREATMENT OF PETS AND SERVICE ANIMALS IN EMERGENCY SITUATIONS - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
During the catastrophic floods that hit the Republic of Serbia in May 2014, a large number of animals suffered. The Law on Emergency Situations 2009, which was in force then, although norming a solid legal mechanism which should have protected animals, evidently did not function in practice. The most noticeable issues in the application of this statutory text that surfaced during the May floods are the following: absence of any activities by the competent ministries directed to preparation and organisation of appropriate courses and seminars, as well as no publishing of any brochures concerning the actions of owners or associations for the protection of animals in the event of natural disasters; inadequate engagement of the entities obliged to protect animals during the floods under the Law; non-existence of regional rescue teams within the Emergency Sector, specially trained to rescue animals at the time of natural disasters; non-existence of expert-operative teams for the evacuation of animals under the emergency headquarters; non-existence of resident civil protection units for the rescue of animals; nonregulation of specific animal rescue procedures from endangered areas in the protection and rescue plans in emergency situations; refusal of rescue crews to save pets and their owners at the same time, as well as non-existence of shelters, where both pets and their owners would stay during a natural disaster. During the May floods, the regulations directly concerning animal protection, such as the Veterinary Law and the Animal Welfare Law of the Republic of Serbia, had no better application either. For instance, due to non-marking or improper marking and registration of owned dogs and cats, a large number of these animals could not have been found in the flooded areas. Meanwhile, the Law on Disaster Risk Reduction and Emergency Management was adopted in 2018. Our attention is focused, in the first place, on the solutions of this statutory text, aimed at establishing whether and to what extent the Serbian legislator made an effort to spot the stated problems and showed good will to regulate them legally.